2020
DOI: 10.1016/j.tips.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Axons Matter: The Promise of Treating Neurodegenerative Disorders by Targeting SARM1-Mediated Axonal Degeneration

Abstract: Attempts to develop neuroprotective treatments for neurodegenerative disorders have not yet been clinically successful. Axonal degeneration has been recognized as a predominant driver of disability and disease progression in central nervous system (CNS) diseases such as amyotrophic lateral sclerosis (ALS), multiple sclerosis, and Parkinson's disease, peripheral nervous system (PNS) disorders such as chemotherapy-induced, diabetic, and inherited neuropathies, and ocular disorders, such as glaucoma. In recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 120 publications
(166 reference statements)
1
78
0
Order By: Relevance
“…While NMNAT1 gene replacement is a potential treatment option for LCA9, if SARM1 plays a more general role in retinal degeneration, then using gene therapy to express this dominant negative SARM1 could not only treat LCA9, but also multiple retinal neurodegenerative diseases. In addition, SARM1 is an enzyme and so small molecule enzyme inhibitors would be another attractive treatment modality ( DiAntonio, 2019 ; Krauss et al, 2020 ). These findings demonstrate the utility of dissecting the molecular mechanism of degeneration in diseases of retinal neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NMNAT1 gene replacement is a potential treatment option for LCA9, if SARM1 plays a more general role in retinal degeneration, then using gene therapy to express this dominant negative SARM1 could not only treat LCA9, but also multiple retinal neurodegenerative diseases. In addition, SARM1 is an enzyme and so small molecule enzyme inhibitors would be another attractive treatment modality ( DiAntonio, 2019 ; Krauss et al, 2020 ). These findings demonstrate the utility of dissecting the molecular mechanism of degeneration in diseases of retinal neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, photoreceptor neurodegeneration in LCA9 shares a deep mechanistic similarity to the pathological axon degeneration pathway. Since the SARM1 pathway is likely druggable ( DiAntonio, 2019 ; Krauss et al, 2020 ), these findings provide a framework for developing new therapeutic strategies for treating patients with LCA9 and potentially other retinal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…While NMNAT1 gene replacement is an exciting treatment option for LCA9, if SARM1 plays a more general role in retinal degeneration, then using gene therapy to express this dominant negative SARM1 could not only treat LCA9, but also multiple retinal neurodegenerative diseases. In addition, SARM1 is an enzyme and so small molecule enzyme inhibitors would be another attractive treatment modality 40,41 . These findings demonstrate the utility of dissecting the molecular mechanism of degeneration in diseases of retinal neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, photoreceptor neurodegeneration in LCA9 shares a deep mechanistic similarity to the pathological axon degeneration pathway. Since the SARM1 pathway is likely druggable 40,41 , these findings provide a framework for developing new therapeutic strategies for treating patients with LCA9 and potentially other retinal disorders.…”
Section: Nmnat1 Plays Important Roles In Diverse Retinal Functions Omentioning
confidence: 96%
“…Multiple studies have demonstrated that SARM1 is a key part of a highly conserved axonal death pathway that is activated by nerve injury (17,18). Importantly, recent studies have shown that SARM1 deficiency confers protection against axonal degeneration in several models of neurodegenerative conditions (6,7,19,20), making SARM1 a compelling molecular target for the development of safe and effective pharmacological therapy to protect axons in a variety of axonopathies (8).…”
Section: Introductionmentioning
confidence: 99%